Factors influencing health-related quality of life in patients with Barrett's esophagus: a qualitative focus group study. Issue 2 (February 2022) - van der Ende-van Loon, Mirjam; Brouwers, Marleen; de Munnik, Suzanne; Nieuwkerk, Pythia; Curvers, Wouter; Schoon, Erik
Abstract : Introduction: Barrett's esophagus is a premalignant condition in the lower part of the esophagus, caused by gastroesophageal reflux disease. Previous studies found that having a Barrett's esophagus is associated with a significant decrease of health-related quality of life (HRQOL). Over the past decade, a considerable amount of literature has been published on the development of endoscopic treatment for (early) neoplasia in Barrett's esophagus. Though, currently very little is known about the impact of those endoscopic treatments on HRQOL from the perspective of patients. In this study, we aim to assess the factors influencing HRQOL according to Barrett's esophagus patients. Methods: By using a qualitative focus group design, patients with nondysplastic Barrett's esophagus and patients with a history of endoscopic treatment for Barrett's dysplasia were included. Data were analysed following the conventional content analyses approach. Results: A total of 34 patients participated in the four focus group sessions. Experiencing symptoms was valued as the most important factor in both groups. Other factors identified as important HRQOL influencers were: use of medication, fear of cancer and trust in physicians and endoscopic procedures. Conclusions: In general, Barrett's esophagus patients experienced a good HRQOL, with a minimal emotional burden from the diagnosis of Barrett's esophagus. Most influencing factor on HRQOL was: experiencing reflux and dyspepsia symptoms. This study underlines the importance of adequate gastroesophageal reflux treatment and providing information to Barrett's esophagus patients, tailored to their personal needs.